Pengaruh Kinerja Keuangan dan Makroekonomi terhadap Return Saham Perusahaan Property dan Real Estate di BEI Periode 2014-2017 - Rina Nugraheni; R.A Sista Paramita (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
This study aims to provide empirical evidence related to the effect of financial and macroeconomic performance on stock returns. Samples were taken using a purposive sampling technique and found 171 companies that routinely report financial reports, did not do a stock split, and did not conduct an IPO during 2014-2017. The data analysis technique used in this study was a multiple regression analysis using the SPSS 23 application. The results showed that simultaneous independent variables influence stock returns. Partial test results in this study showed that financial performance variables that were proxied by the Current ratio, PER, DER, PBV, and TATO did not affect stock returns, while macroeconomics (inflation and exchange rates) had a significant negative effect on stock returns. Macroeconomic factors are more influential on stock returns and responded by investors directly suitable for short-term investments, while financial performance requires time to be responded by stock returns and more suitable for long-term investments.